Penerapan Validitas pada Materi Pecahan sebagai Inovasi Pembelajaran Tematik pada Siswa Kelas III di SDN Jatake 5 Kota Tangerang - Ina Magdalena; Wila Indah; Inka Septiana; Dinda Aprilia; Amalia Dwi Listyana (Jurnal Halaqah, 2020)
Mathematics is a subject that is feared by the majority of students, especially elementary school students. This is because abstract mathematical material is also presented abstractly. Mathematics for elementary school students must be presented concretely so that it can be understood by students. One of the mathematical material is the fraction operation. The material is often presented abstractly with a formula so that students do not understand the meaning of the material. The impact is that many students have difficulty doing the fractional counting operations, especially the counting operations of the fractions which are not the same. Currently, in the learning process, students use thematic teaching materials where fractions are included in thematic learning. In the development process, there is also a validity stage where the validity of this test is a test of fractional thematic learning conducted by three people namely the material expert.